Disinfection of External Environment Objects to Parasitic Protozoa Cysts (Buxtonella sulcatа) in Cattle - R. T. Safiullin; S. K. Shibitov (Российский паразитологический журнал, 2020)
The purpose of the research is to develop the method of disinfection of external environment objects against cysts Buxtonella sulcata in cattle.Materials and methods. Under the conditions of "Orlovskoe” OJSC of Shchyolkovsky District Moscow Region biological test for experimental infection was applied for determination of efficiency of Cystodez for disinfection on 30 calves at the age of 6 months, which were free of B. sulcata. Efficiency of disinfection in the course of prescribing different concentrations of Cystodez as well as 4% concentration of background drug of carbolic acid was determined based on the percentage reduction of generation B. sulcata cysts after the above stated drugs exposure and concentrations compared with infected control calves, which were prescribed 200 cysts/ml. During August–September 2017 efficiency of 4% Cystodez against B. sulcata cysts of cattle were tested by the mean of by artificial laying of B. sulcata cysts on control sites compared with the background drug of 4% carbolic acid within the exposure of 2 hours under the manufacturing conditions of OJSC named after Guryanov of the Kaluga Region.Results and discussion. Intensive efficiency of 3% concentration of Cystodez was 97.9%, and in 4 and 5% concentration the drug demonstrated 100 % efficiency. Results received during manufacturing testing of 4 % Cystodez at the dose of 0.5 l per 1 m 2 within the exposure of 2 hours show its high efficiency for disinfection against cysts of cattle B. sulcata. Intensive efficiency was 92.32% versus 75.6% efficiency of the 4% background drug of carbolic acid.